Genome Wide Identification and Expression Profiling Indicate Expansion of Family I84 Protease Inhibitor via Gene Tandem Duplication and Divergence in Razor Clam Sinonovacula constricta - Liu, Sheng; Liu, Youli; Lu, Jiali; Mao, Jinxia; Lin, Zhihua; Xue, Qinggang (Frontiers in Immunology, 2022)
Family I84 protease inhibitors represent a novel family in the MEROPS peptidase database and are likely unique for molluscan host defense. Two Family I84 members, scSI-1 and scSI-2, were reported from the razor clam Sinonovacula constricta in a previous research. In the present study, 12 additional genes, named scSI-3 to scSI-14, were identified via genome wide sequence analyses. Among them, 10 genes were predicted to have a signal sequence, but one (scSI-7) was not. Besides, one sequence (scSI-14) was likely to encode a prematurely terminated peptide. The predicted mature peptides shared characteristics including 12 conserved cysteine residues, isoelectric points of 4.98 to 6.11, and molecular weights of 7.1 to 9.3 kDa with previously reported family members. Four motifs were characterized in 13 predicted mature peptides (with exception of scSI-14), which shared two to four conserved cysteine residues, are possibly to form two functional domain comprised 6 cysteine residues, respectively. At genomic level, all the 14 razor clam Family I84 genes were organized into 3 exons and 2 introns; 13 of them clustered in 3 regions of 100 kb on 3 separate chromosomes, suggesting tandem duplications of related genes. The promoter region of all the 14 genes was predicted to share some transcription factor binding sites, in particular those responsive to pathological and physiological stimuli, but no shared motifs were identified. Analyses also revealed differences in expression patterns among the genes. One gene in a tandem duplicated gene pairs usually showed a higher expression level than the other whereas non-tandem duplicated genes exhibited a higher degree of correlation in expression level. In addition, 8 of the 14 genes demonstrated higher level of expression in Vibrio tolerant clams than in non-tolerant clams following challenges with Vibrio parahaemolyticus. These results generated important information about the evolution of Family I84 protease inhibitors in S. constricta.